The Effect of Video Content Generation on the Speaking Development of Pre-Service EFL Teachers - Yürük, Süleyman E.; Yilmaz, Rabia (My University, 2025)
This study explores the impact of Video Content Generation (VCG) activities on the foreign language development of pre-service teachers. The research employs a mixed-methods approach, with a quantitative stage utilizing a single-group pre-test/post-test design and a qualitative stage employing a case study approach. The study involves 30 students tasked with VCG activities. Three experts assessed their speaking development (fluency, grammar, pronunciation, vocabulary, organization) using a rubric over eight weeks. The weekly scores obtained were analyzed using a repeated measures ANOVA test. Significant improvements were observed in fluency, vocabulary, pronunciation, and organization scores, particularly in later weeks, with medium to large effect sizes. However, grammar scores did not show significant differences. Qualitative data from focus group interviews with 11 female and 6 male students highlight the perceived benefits of VCG, particularly in terms of enhanced fluency and pronunciation practice. According to the interview findings, students stated that producing video content provided an opportunity to practice speaking outside the classroom, enabling them to speak more fluently and with more accurate pronunciation in front of a camera and an audience. They expressed positive feelings about having their own video channel. However, they also reported experiencing difficulties throughout various stages of the video production process, including selecting a topic, ensuring suitable conditions for recording, facing challenges during filming, and dealing with editing and sharing the videos. The study concluded that producing video content significantly improved students’ speaking skills, and several suggestions were offered for English teachers to incorporate video content production into their classroom practices.
Keywords: Teacher education; social media; speaking development; student-generated content; video content generation